Effect of Zn addition on two-step aging behaviour of Al–Mg–Si–Cu alloy. Issue 10 (3rd July 2019) - Zhu, Shang; Li, Zhihui; Yan, Lizhen; Li, Xiwu; Huang, Shuhui; Yan, Hongwei; Zhang, Yongan; Xiong, Baiqing
ABSTRACT: This study investigates the effect of Zn addition two-step behaviour in an Al–Mg–Si–Cu alloy. During pre-aging at 100°C for 3 h, the Zn can partition into clusters because of the strong Zn–Mg interaction, prompting the formation of clusters. During subsequent artificial aging at 180°C for up to 240 min (peak hardness condition), the Zn does not significantly partition into clusters or precipitates, and the majority of Zn remains in the Al matrix. However, the presence of Zn in the matrix stimulates the transformation from clusters to GP zones to β′′ phases. The enhanced formation of GP zones and β′′ phases correlates well with the remarkable age-hardening response.